Adoption Behavior of FLD and Non-FLD Farmers of Sunflower (Indian Journal of Extension Education, 2009)
Sunflower crop has a comparative advantage over other annual oilseed crops due to its wider adaptability. Its cultivation is chiefly confined to Karnataka, Andhra Pradesh and Maharashtra. The reasons for poor yields are manifold of which the important one is non-adoption of recommended technology. In order to demonstrate the potentials of the proven technologies of sunflower in the state, the All India Coordinated Research Project (AICRP) on sunflower at Latur organized the frontline demonstrations (FLD) on sunflower production technology and the present study was undertaken to assess their impact on adoption behaviour of FLD and non- FLD farmers to identify the constraints encountered and elicit suggestions as perceived by them. Despite, the fact that the FLD farmers have not resorted to 100 per cent of the components under the FLDs conducted in the region, they were still able to ealize additional income of Rs. 2094/ha. There were a host of constraints which include both biological and socio-economic standing in the way of increasing the productivity.